Health and safety challenges in medical entities and the powers of the social labor inspector: Lessons related to the COVID-19 outbreak in the context of internal control of employee health and safety - Maciej Jarota (Nofer Institute of Occupational Medicine, 2023)
Employees in the medical profession in a situation where the life of a patient is at risk cannot refrain from working due to unsafe working conditions. Therefore, enforcing the right to safe and hygienic working conditions is particularly important so that employees can provide health care services without additional burdens. The purpose of the study is to determine how the social labour inspector can respond to Occupational Health and Safety (OHS) hazards and whether the current powers of the social labor inspectorate as the employer's internal OHS control body are sufficient. The study conducted a regulatory analysis and used relevant literature, including recent studies on law enforcement. In addition, a questionnaire survey was conducted among trade union representatives of medical professionals on the evaluation of social labour inspector activities and OHS hazards during the COVID-19 epidemic period. In this period characterized by many OHS risks in medical entities, the difficulties faced by employers in carrying out their duty to protect the health of their employees became apparent. The system of internal control with the participation of the social labour inspection in this context needs changes, due to the fact that it is used in an inefficient manner. The reasons for this are primarily incomplete legal regulations. The legislator should guarantee the social labour inspector the right to use both methods of rewarding the employer as an incentive for the proper performance of duties and measures to deter violations of the law. Despite the fact that Polish labour law guarantees mechanisms for OHS control by the social labour inspector, it would be appropriate to expand the catalog of measures used by him to effectively motivate employers to protect worker health. This study is a prelude to a broader discussion of OHS monitoring in the context of OHS hazards occurring in healthcare entities. Med Pr Work Health Saf. 2023;74(4):301-16.